Primary Osteosarcoma of the Breast: A Rare Case Report and Literature Review - Li, Shike; Xue, Qingfeng; Shi, Wenyu (Frontiers in Oncology, 2022)
Background: Primary osteosarcoma of the breast (POB) is an extremely aggressive, and heterogeneous neoplasm, which originates from nonepithelial elements of the mammary gland and accounts for fewer than 1% of breast cancers and fewer than 5% of all sarcomas. Case Presentation: An 83-year-old Chinese female went to our hospital because of a palpable mass for 8 months in the left breast accompanied by persistent dull pain for 10 days. This mass was initially misdiagnosed as a degenerating fibroadenoma and was graded as probably benign (BI-RADS category 3) by US and CT plain scan and contrast enhancement of chest. 8 months later, it was presumed to be highly malignant and graded as BI-RADS category 4C because of its rapid growth and more calcifications by US and CT. 99mTc-MDP whole body bone imaging showed that there was a mass-like abnormal radioactive concentration of Tc-99m outside the bone of the left chest. The lumpectomy of the left breast was indicated, and the pathological findings were POB. She succumbed to respiratory failure caused by multiple lung metastases 4 months after the operation. Conclusion: POB is rare, US and CT cannot reliably distinguish the causes of calcified breast masses between benign and malignant tumors. It can be diagnosed by pathology, and it can also be determined when an osteogenic sarcoma originating from the underlying bone is excluded and immunohistochemistry shows positivity for vimentin. This case could help clinicians to improve the prognosis and treatment of this disease.